ANALISIS PENGGUNAAN DAN MAKNA DIKSI YANG TERDAPAT PADA LIRIK LAGU “RESAH” PAYUNG TEDUH - Rizky Azis Mubarok; Yusup Yusup; Ai Siti Zenab (IKIP Siliwangi, 2018)
Language and Art literature when combined with other arts such as musical instruments, will make a work of art that has a high aesthetic value. Although the work has become mixed art because of the form of poetry sung or song lyrics. By using the media in the form of art, it is expected that the learning objectives can be treated well. Researchers use the object of research in the form of song lyrics. The purpose of this research is to know the language or the selection of words used on the lyrics of the band's shaky receptive band. The reason for taking the title, because the language aspect is one of the most important elements used by poets in literary arts as in the literary works of poetry. This research is a qualitative descriptive study. Assessment of the objects of this study using analytical techniques with data collection techniques, using literature research techniques. The data analysis technique begins by reading all the lyrics of the song to be analyzed, then finding the choice of word or diction choice contained in the lyrics of the song. Next understand the meaning of the song lyrics, then last make a conclusion. The researchers got the result that there are some diction used in the lyrics of the song shrill umbrella shade, including: In the rain and dark night, But I can not see your eyes, Among the deciduous leaves, Wobbles of the wind, waiting for the body.